Genetic Variation of an Odorant Receptor OR7D4 and Sensory Perception of Cooked Meat Containing Androstenone - Lunde, Kathrine; Egelandsdal, Bjørg; Skuterud, Ellen; Mainland, Joel D.; Lea, Tor; Hersleth, Margrethe; Matsunami, Hiroaki (PLOS ONE, 2012)
Although odour perception impacts food preferences, the effect of genotypic variation of odorant receptors (ORs) on the sensory perception of food is unclear. Human OR7D4 responds to androstenone, and genotypic variation in OR7D4 predicts variation in the perception of androstenone. Since androstenone is naturally present in meat derived from male pigs, we asked whether OR7D4 genotype correlates with either the ability to detect androstenone or the evaluation of cooked pork tainted with varying levels of androstenone within the naturally-occurring range. Consistent with previous findings, subjects with two copies of the functional OR7D4 RT variant were more sensitive to androstenone than subjects carrying a non-functional OR7D4 WM variant. When pork containing varying levels of androstenone was cooked and tested by sniffing and tasting, subjects with two copies of the RT variant tended to rate the androstenone-containing meat as less favourable than subjects carrying the WM variant. Our data is consistent with the idea that OR7D4 genotype predicts the sensory perception of meat containing androstenone and that genetic variation in an odorant receptor can alter food preferences.